Mechanism of CO2 conversion into methanol and methane at the edge of graphitic carbon nitride sheet: A first-principle study. (November 2020) - Wu, Hong-Zhang; Bandaru, Sateesh; Liu, Jin; Li, Li-Li; Jin, Lin
Abstract: Rational conversion of CO2 into valuable fuels would partially or fully close the carbon loop and can have significant environmental benefits. The elemental steps of CO2 conversion into hydrocarbon fuels such as methanol, methane and a series intermediates at the edge of graphitic carbon nitride were investigated using first-principle calculations. Herein, we reported the detailed mechanism of CO2 reduction at the edge of g-C3 N4 sheet including two possible pathways based on H-shuttling model. The participation of hydrogen within NH group at the edge of g-C3 N4 sheet as another hydrogen source could promote the hydrogenation of intermediate through the rearrangement reaction. Methanol is a quite favorable product than methane during CO2 reduction reaction. Carbon monoxide (CO) and formaldehyde as the products would limit the conversion of CO2 to hydrocarbon fuels. Graphical abstract: Image 1